Ocena wpływu zastosowania metody Ora na poprawę wybranych wskaźników stabilometrycznych i posturometrycznych u dziewcząt z zaburzeniami statyki ciała = Evaluation of the impact of Ora method on the improvement of selected stabilometric and posturometric factors in girls with body statics problems - Bibrowicz, Karol; Szurmik, Tomasz; Mrozkowiak, Mirosław (Journal of Education, Health and Sport, 2016)
Bibrowicz Karol, Szurmik Tomasz, Mrozkowiak Mirosław. Ocena wpływu zastosowania metody Ora na poprawę wybranych wskaźników stabilometrycznych i posturometrycznych u dziewcząt z zaburzeniami statyki ciała = Evaluation of the impact of Ora method on the improvement of selected stabilometric and posturometric factors in girls with body statics problems. Journal of Education, Health and Sport. 2016;6(12):84-97. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.192389 http://ojs.ukw.edu.pl/index.php/johs/article/view/4037 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.11.2016. Revised 22.11.2016. Accepted: 02.12.2016. OCENA WPŁYWU ZASTOSOWANIA METODY ORA NA POPRAWĘ WYBRANYCH WSKAŹNIKÓW STABILOMETRYCZNYCH I POSTUROMETRYCZNYCH U DZIEWCZĄT Z ZABURZENIAMI STATYKI CIAŁA EVALUATION OF THE IMPACT OF ORA METHOD ON THE IMPROVEMENT OF SELECTED STABILOMETRIC AND POSTUROMETRIC FACTORS IN GIRLS WITH BODY STATICS PROBLEMS Karol Bibrowicz 1,2, Tomasz Szurmik 3,4, Mirosław Mrozkowiak 5 1 Wyższa Szkoła Edukacji i Terapii w Poznaniu 2 Centrum Edukacji i Terapii Habitus Wrocław – Lutynia 3 Uniwersytet Śląski, Wydział Etnologii i Nauk o Edukacji w Cieszynie 4 Orto-Med Bielsko-Biała 5 Bioergosport Nowa Biała Karol Bibrowicz 1,2, Tomasz Szurmik 3,4, Mirosław Mrozkowiak 5 1College of Education and Therapy in Poznań 2Center of Education and Therapy Habitus Wrocław — Lutynia 3University of Silesia, Faculty of Ethnology and Educational Science in Cieszyn 4 Orto-Med Bielsko-Biała 5 Bioergosport Nowa Biała Streszczenie Cel. W prezentowanym doniesieniu podjęto problem oceny wpływu zastosowania metody ORA na poprawę wybranych wskaźników stabilometrycznych i posturometrycznych u dziewcząt z zaburzeniami statyki ciała. Metoda. Badaniami objęto 40 osobową grupę dziewcząt w wieku od 12 do 16 lat ze stwierdzonymi zaburzeniami statyki ciała. Dla oceny wpływu Metody ORA na badane zmienne, badaną grupę podzielono losowo na dwie dwudziestoosobowe podgrupy: badawczą, z dodatkowymi ćwiczeniami z aparatem ORA oraz kontrolną. Program badań obejmował ocenę zmian ustawienia głowy w płaszczyźnie strzałkowej i czołowej oraz zmian kontroli stabilności posturalnej. Wszystkie dziewczęta miały dwukrotnie przeprowadzone badania stabilometryczne z wykorzystaniem dwupłytowej platformy balansowej CQ-electronic oraz fotometryczną analizę postawy z wykorzystaniem Systemu Fotograficznej Analizy Postawy Ciała (SFAPC). Wyniki: Zastosowana terapia przyniosła pozytywne zmiany wszystkich parametrów w obu badanych grupach. Zaobserwowano bardziej wyraźną poprawę ustawienia głowy w przestrzeni w grupie badawczej, szczególnie w parametrze kąta nachylenia Głowy (KNG) gdzie te zmiany były istotne. Stwierdzono również istotne zmiany w grupie badawczej dotyczące całkowitej długości ścieżki (SP) i długości ścieżki w płaszczyźnie czołowej (SPML). Wnioski: 1. Analiza zmiennych charakteryzujących przestrzenne ustawienie głowy wskazuje na tendencję do poprawy jej ustawienia w badaniach kontrolnych w obu grupach. Wyraźniejsze zmiany obserwowano w grupie z aparatem ORA. 2. Istotną poprawę stwierdzono wyłącznie dla kąta nachylenia głowy KNG w grupie z aparatem ORA. 3.Analizowane zmienne stabilograficzne również wykazały tendencję do poprawy w obu badanych grupach. W grupie badawczej ta tendencja była także wyraźniejsza. 4. Istotne zmiany stwierdzono dla całkowitej długości ścieżki (SP) i długości ścieżki w płaszczyźnie czołowej (SPML) w grupie badawczej. Słowa kluczowe: równowaga, postawa ciała, zgryz, stawy skroniowo-żuchwowe. Abstract Objective. The paper presents the problem of evaluation of the impact of ORA method on the improvement of the selected stabilometric and posturometric factors in girls with body statics problems. Method. The tests were conducted in a group of 40 girls, age 12 to 16, with diagnosed body statics problems. In order to evaluate how the ORA Method affects the studied variables, the sample was randomly divided in two groups of 20: a tested group and a control group. The examination program involved the evaluation of changes of the head position in the sagittal plane and in the frontal plane as well as changes of control of postural stability in both studied groups. Stabilometric tests by means of two-board CQ-electronic balance platform and photometric posture analysis using the System of Photographic Analysis of Postural Control (SFAPC, System Fotograficznej Analizy Postawy Ciała) were applied twice on all girls. Results: The applied therapy resulted in positive changes of all parameters in both studied groups. A definite improvement of the spatial head position has been noticed in the tested group, particularly for the head inclination angle (KNG, kąt nachylenia głowy) parameter, where these changes were significant. There were also significant changes in the tested group regarding total length of the sway path (SP) and path length in the frontal plane (Sway Path Medium-Lateral, SPML). Conclusions: 1. The analysis of the variables that characterize the spacial head position shows a tendency to improve the head’s position in the control tests, both in the group in which ORA device was used and in the control group. The improvement was more observable in the group using the ORA device. 2. Statistically relevant improvement was noticed only for the head inclination angle KNG in the group with the ORA device. 3. The analyzed stabilographic variables also showed the tendency to improve in both studied groups. However, in the group using ORA devices, this tendency was also more noticeable. 4. Statistically significant changes in the values of the studied variables were observed for total sway path (SP) length and frontal plane path (SPML) length in the group using ORA devices. Keywords: balance, body posture, occlusion, temporomandibular joints.